Intermittent fasting promotes repair of rotator cuff injury in the early postoperative period by regulating the gut microbiota - Shanshan Xie; Changbiao Guan; Tingmo Huang; Yuqian Liu; Feifei Yuan; Daqi Xu (Journal of Orthopaedic Translation, 2022)
Background: The repair of rotator cuff injury is affected by lifestyle and metabolic factors. Intermittent fasting (IF) can promote repair of damaged tissue by regulating intestinal flora, which provides an idea of therapy for rotator cuff injury. The aim of this study was to investigate the effects of fasting on rotator cuff repair after injury, and the role of intestinal flora or a single strain in this process. Methods: Mice underwent rotator cuff injury were treated with intermittent fasting or fed ad libitum. Fasting began one month before surgery and continued until euthanasia. Fresh feces were collected at 2 weeks before surgery, on the day of surgery, and 2, 4, 8 weeks postoperatively for 16S rRNA microbiome sequencing. Supraspinatus tendon-humerus ​(SSTH) complex was collected at 2, 4 and 8 weeks after surgery. Live parabacteroides distasonis (Parabacteroides distasonis) was used for repair of rotator cuff injury, with equal amount of pasteurized P. distasonis (KPD) or sterile anaerobic phosphate buffer saline (PBS) as control. Biomechanical, radiological, histological analysis were used to assess the effect of rotator cuff repair. Results: Biomechanical, radiological and histological analysis indicated that intermittent fasting significantly promoted the repair of rotator cuff injury in the early postoperative period (P ＜ 0.05), but significantly inhibited the repair of rotator cuff injury at 4 weeks postoperatively (P ＜ 0.05). 16S rRNA Microbiome sequencing result showed that P. distasonis was the species with the most obvious changes in intestinal flora of mice after fasting. The results of tensile test, X-ray analysis and histological analysis indicated that the live P. distasonis (LPD) significantly impaired the biomechanical properties, bone regeneration and fibrocartilage regeneration of enthesis postoperatively (P ＜ 0.05). Conclusion: Intermittent fasting promoted repair of rotator cuff injury in the early postoperative period by regulating the gut microbiota, in which P. distasonis played an important role. The translational potential of this article: Intermittent fasting (IF) may be a beneficial lifestyle for the repair of rotator cuff injury in the early postoperative period in clinical, and the influence of a certain strain on the repair of rotator cuff injury may also provide an idea for the treatment of rotator cuff injury in the future.